2018
DOI: 10.1001/jamasurg.2018.0380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rates and Outcomes of Readmission to Index vs Nonindex Hospitals After Major Cancer Surgery

Abstract: Approximately one-fifth of readmissions were to a nonindex hospital and were associated with higher mortality and morbidity than readmission to index hospitals. Factors that influence nonindex readmissions have been identified to target interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 27 publications
4
33
2
Order By: Relevance
“…10,[16][17][18][19][20] Our readmission rates are also comparable to those of major cancer surgeries (eg esophagectomy, gastrectomy, hepatic or pancreatic resection, lung resection, colectomy, cystectomy), found in multiple retrospective studies. [21][22][23][24] Similar to many of these studies, among women with high-grade serous ovarian cancer, while the mortality rate in our paper was 1.7%. 25 While there is a difference between these values, it is likely secondary to the variability in information available in this database, and these results do not impact the conclusions of our study.…”
Section: Predictors Of 30-and 90-day Readmissionsupporting
confidence: 83%
“…10,[16][17][18][19][20] Our readmission rates are also comparable to those of major cancer surgeries (eg esophagectomy, gastrectomy, hepatic or pancreatic resection, lung resection, colectomy, cystectomy), found in multiple retrospective studies. [21][22][23][24] Similar to many of these studies, among women with high-grade serous ovarian cancer, while the mortality rate in our paper was 1.7%. 25 While there is a difference between these values, it is likely secondary to the variability in information available in this database, and these results do not impact the conclusions of our study.…”
Section: Predictors Of 30-and 90-day Readmissionsupporting
confidence: 83%
“…Studies examining other disease states and procedures have identified fragmentation of care as an important factor affecting patient outcomes. These reports conclude that readmission to a non-index hospital results in higher rates of morbidity and mortality 13–18. Our results, however, do not follow this pattern.…”
Section: Discussioncontrasting
confidence: 68%
“…There is limited information on whether functional outcomes after discharge vary according to readmission destination. Taking appropriate measures to prevent complications in patients undergoing mechanical thrombectomy and managing complications when they arise are essential for an effective continuum of stroke care 13…”
Section: Introductionmentioning
confidence: 99%
“…These patients often require early stabilization, and moving to the nearest hospital may be the most appropriate measure in this situation. 19 As a result, healthcare workers will face the challenge of deciding whether to divert patients to the nearest emergency department of a different hospital or to the index hospital. A study based on the Danish population reported that low socioeconomic status was associated with higher risk of bacteremia and increased mortality, compared to high socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%